Do Resin Cements Alter Action Potentials of Isolated Rat Sciatic Nerve? - Ertan, Ahmet Atila; Beriat, Nilufer Celebi; Onur, Mehmet Ali; Tan, Gamze; Cehreli, Murat Cavit (European Journal of Dentistry, 2011)
Objectives: The purpose of this study was to explore the effects dual-cure resin cements on nerve conduction. Methods: Panavia F, RelyX ARC, and Variolink II polymerized either by light-emitting diode (LED) or quartz tungsten halogen (QTH) were used in the study (n=10). The conductance of sciatic nerves of 50 rats were measured before and after contact with the specimens for 1 h. Results: The time-dependent change in nerve conductance and the comparison of LED versus QTH showed that differences between groups are significant (P&.05). For both polymerization techniques, pair-wise comparisons of resin cements showed that the nerve conductance between groups is different (P&.05). RelyX ARC elicited irreversible inhibition of compound action potentials (more than 50% change) and Panavia F and Variolink II polymerized by LED and QTH did not alter nerve conduction beyond physiologic limits. Conclusions: Resin cements may alter nerve conductance and even lead to neurotoxic effects. (Eur J Dent 2011;5:199-205)
Keywords: Resin cement; Light-emitting diode; Quartz tungsten halogen; Neurotoxicity; Rat; Sciatic nerve